Faith-based paths to business success: Malaysian manifestations of the evangelical-neoliberal nexus / Martin Králik - Martin , Králik (2020)
The thesis profiles a number of evangelical Christian groups which operate in Malaysia’s Klang Valley. Some of them have embraced business, financing, investment and real estate undertakings on a significant scale. The objective was to cast new light on how the confluence of evangelical and neoliberal capitalist forces (occurring first in the United States and now transnationally) influenced and at times directly shaped their setting up, development and growth, as well as broader socioeconomic and political positions. In particular, the aim was to map out and analyse the founders’ and members’ choice of religious affiliation; their personal motivations and the sociological formations they represent; the churches’ approach to marketing themselves to the community and other community outreach; and the groups’ entry into and participation in business, which has come with its own sets of governance structures and requirements. Conceptualizations of the dynamics and implications of the rising nexus of neoliberal and evangelical-Christian discourses are a young and underdeveloped field of social research. Despite its relevance to political economy as well as the emerging sub-discipline of sociology of commodification of religion, there is great paucity of literature on the topic. Therefore, fresh empirical data can fill many gaps, especially when it is situated in the context of a developing and multi-ethnic, multi-religious society. This data is presented in the form of case studies, portraying a cross-section of Malaysia’s urban evangelical community. Reflecting the nature of the material, our methodological approach is rooted in detailed empirical inquiry enriched with elements of large-scale social analysis. Academics have been in agreement that it is the hallmark of neoliberalism to commoditize all social relations including religion. Drawing on theories of commoditization and on organizational theory, this study examines the paradigm of churches as owners and distributors of “religious goods” targeted at specific segments of consumers. Also outlined here is how this distribution necessarily entails such processes as competition and specialization among groups. Upon completing archival and interview portions of the data collection, the research effort proceeded to a thematic, explanatory analysis of the main findings, linking fragmentary data to larger assertions and organizing these into coherent case studies. Throughout this process, the analysis was informed by an awareness of the contested nature of this research territory and of the possibility that different views and concepts revealed by the sources may compete and negotiate with each other. This study traces how the churches’ activities led to the creation of new social spaces, organized around notions of social attachment and belonging that resonate with a society undergoing neoliberal change. Also documented here are the newly porous boundaries between church and corporation; social good and profit; and worshippers and shareholders. Lastly, this study puts forward the emerging picture of a religious economy and discusses its ramifications for interacting with other groups, other religions and with the state.